Penentuan Portofolio Optimal Dengan Model Markowitz Pada Saham Perbankan di Bursa Efek Indonesia - Indrayanti, Ni Wayan Yuli; Darmayanti, Ni Putu Ayu (E-Jurnal Manajemen, 2013)
Fund investment activities in the capital market required expertise to minimize the investment risk. One way was to form a portfolio. Markowitz model helped investors determined the stocks which was the member of the optimal portfolio. Minimization of risk and maximization of return became the urgent thing, and the value of the return expectation became the basis of calculation. This research used purposive sampling to select 15 banking at BEI that had a high value of Price Earning Ratio. Results showed that only 5 (five) banks were included in the optimal portfolio, which was BSWD ( Bank Of India Indonesia Tbk), BEKS (Bank Pundi Indonesia Tbk), MAYA (Bank Mayapada Internasional Tbk), BTPN (Bank Tabungan Pensiunan Nasional Tbk), and BBNI (Bank Negara Indonesia (Persero) Tbk) . The optimal investment portfolio provided total expected return portfolio was 2.135 percent and a risk of deviation / variance portfolio was 0.293 percent. Keyword: investasi, portofolio optimal, model Markowitz, PER (Price Earning Ratio)